Development of Educational Game-Based Student Worksheets on Reproductive System Materials to Improve Student Interest and Learning Outcomes (Journal of Biology Education, 2023)
Learning media is an important thing that plays a very important role in the learning process in the classroom. Based on the results of the interview, it is known that the learning media at SMA N 1 Kendal still uses limited sources, namely package books and Student Worksheets which are still conventional. The speaker mentioned that one of the materials that were considered difficult was the Reproductive System material. The development of educational game-based Student Worksheets (LKPD) is needed to overcome problems that arise. This study aims to determine the validity of LKPD media and the effectiveness of using educational game-based LKPD on Reproductive System material in increasing student interest and learning outcomes. The research was designed with 4D research methods: Define, design, develop, and disseminate. The research design used is a one-group pretest-posttest design. The sampling technique uses the purposive sampling method. The validity of the LKPD developed gets very feasible criteria for use for learning media on the Reproductive System material. The results of LKPD validation obtained a percentage of 89.85% from media experts, and 97.5% from material experts, both of whom are in the very decent category. Validation results by students obtained a percentage of 81.47% with the category of very decent. Analysis of learning outcomes obtained an N-gain score of 74.75% with medium and high categories and for classical completion, students obtained results of 85.04%. Based on the results of research and data analysis that has been carried out, it was concluded that LKPD based on educational games on the Reproductive System material is suitable for use as a learning medium and is effective in increasing student interest and learning outcomes at SMA Negeri 1 Kendal.